Patterns, trends and sex differences in HIV/AIDS reported mortality in Latin American countries: 1996-2007 - Martin Luise (BMC Public Health, 2011)
Abstract Background International cohort studies have shown that antiretroviral treatment (ART) has improved survival of HIV-infected individuals. National population based studies of HIV mortality exist in industrialized settings but few have been presented from developing countries. Our objective was to investigate on a population basis, the regional situation regarding HIV mortality and trends in Latin America (LA) in the context of adoption of public ART policies and gender differences. Methods Cause of death data from vital statistics registries from 1996 to 2007 with "good" or "average" quality of mortality data were examined. Standardized mortality rates and Poisson regression models by country were developed and differences among countries assessed to identify patterns of HIV mortality over time occurring in Latin America. Results Standardized HIV mortality following the adoption of public ART policies was highest in Panama and El Salvador and lowest in Chile. During the study period, three overall patterns were identified in HIV mortality trends- following the adoption of the free ART public policies; a remarkable decrement, a remarkable increment and a slight increment. HIV mortality was consistently higher in males compared to females. Mean age of death attributable to HIV increased in the majority of countries over the study period. Conclusions Vital statistics registries provide valuable information on HIV mortality in LA. While the introduction of national policies for free ART provision has coincided with declines in population-level HIV mortality and increasing age of death in some countries, in others HIV mortality has increased. Barriers to effective ART implementation and uptake in the context of free ART public provision policies should be further investigated.